2020
DOI: 10.1101/2020.04.08.20056713
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MTXPK.org: A clinical decision support tool evaluating high-dose methotrexate pharmacokinetics to inform post-infusion care and use of glucarpidase

Abstract: Methotrexate (MTX), an anti-folate, is administered at high-doses to treat malignancies in children and adults. However, there is considerable interpatient variability in clearance of high-dose (HD) MTX. Patients with delayed clearance are at an increased risk for severe nephrotoxicity and life-threatening systemic MTX exposure. Glucarpidase is a rescue agent for severe MTX toxicity that reduces plasma MTX levels via hydrolysis of MTX into inactive metabolites, but is only indicated when MTX concentrations are… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…PK findings from clinical studies can lead to improvements in therapeutic outcomes through amendments to clinical protocols [ 5 , 15 ] or the development of clinical decision support tools [ 16 ]. It was recently shown that >90% of persons have an actionable drug-gene polymorphism [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…PK findings from clinical studies can lead to improvements in therapeutic outcomes through amendments to clinical protocols [ 5 , 15 ] or the development of clinical decision support tools [ 16 ]. It was recently shown that >90% of persons have an actionable drug-gene polymorphism [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 17 papers were included for extraction of quality markers. Articles included two original article about assessing the quality of reporting of clinical pharmacokinetics studies, 6,9 one systematic review, 10 one mini-review, 11 two organizational reports, 12,13 nine reviews [14][15][16][17][18][19][20][21][22] and two guidelines. 23,24 The included articles discussed the quality markers pertaining to retrospective and prospective clinical pharmacokinetic studies, bioequivalence studies, as well as population pharmacokinetic studies.…”
Section: Included Articles and Characteristicsmentioning
confidence: 99%
“…14 Whereas these examples are illustrative of hypothesis generation for TDM, equally crucial for clinical translation are innovations in model-informed clinical decision support systems for deployment of TDM and downstream patient management in clinical practice. 15 Physiologically-based pharmacokinetic modeling and simulation has steadily driven efficiency in evaluating intrinsic and extrinsic factor effects in drug development to inform dosing and administration across clinical contexts of use, as elegantly demonstrated with the cyclin-dependent kinase 4/6 inhibitor ribociclib. 16 Of note, our understanding of sources of variability in the clinical pharmacology of therapeutics continues to evolve, illustrated in a survey of the impact of hepatic impairment on pharmacokinetics of monoclonal antibodies.…”
Section: Advancing Precision Dosing Is Crucial To Maximize Benefit/rimentioning
confidence: 99%